The Relationship of Burmese High School Students’ Motivation, Perception of Teachers’ with Self-Efficacy in Learning English as a Foreign Language - Aung, Phyo MaMa; Richard Lynch (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this quantitative correlational study was to determine whether there was a significant relationship between Grades 10 and 11 students’ motivation for learning English as a foreign language and perception of teachers’ effectiveness with self-efficacy for learning English as a foreign language at Mingalar Education Center Private High School, Sanchaung, Yangon, Myanmar. A total of 82 Grade 10 and 11 students participated in this study. Related data with motivation, perception toward teachers’ effectiveness and self-efficacy in learning language were gathered through administering a survey questionnaire which was adapted from the international version of Gardner’s (2004) Attitude/Motivation Test Battery and Questionnaire for English Self-efficacy were considered to measure participants’ scales. For the analysis of the collected data, descriptive statistics, and correlational analysis (using multiple correlation coefficient) was used. The findings of the research indicated that there was a significant, positive, and strong relationship between students’ motivation for learning English as a foreign language and their perception toward teachers’ effectiveness for learning English as a foreign language with self-efficacy for learning English as a foreign language. Based on the findings, the researcher provides recommendations for teachers, students, school administrators, Ministry of Education (Myanmar) and future researchers.